Computers and the history of art : a subject in transition - Bentkowska-Kafel, Anna; Cashen, Trish; Gardiner, Hazel (Computers and the history of art, 2005)
This book looks at the transformation that Art and Art history is undergoing through engagement with the digital revolution. Since its initiation in 1985, CHArt (Computers and the History of Art) has set out to promote interaction between the rapidly developing new Information Technology and the study and practice of Art. It has become increasingly clear in recent years that this interaction has led, not just to the provision of new tools for the carrying out of existing practices, but to the evolution of unprecedented activities and modes of thought. This collection of papers represents the v.